Suspicious readings of Joyce's Dubliners - Norris, Margot (UPCC book collections on Project MUSE., 2003)
"Suspicious Readings of Joyce's Dubliners devotes a chapter to each of the fifteen stories in Dubliners and shows how each confronts the reader with an interpretive challenge and an intellectual adventure. Its readings of "An Encounter," "Two Gallants," "A Painful Case," "A Mother," "The Boarding House," and "Grace" reconceive the stories in wholly novel ways - ways that reveal Joyce's writing to be even more brilliant, more exciting, and more seriously attuned to moral and political issues than we had thought."--Provided by publisher.